Changes in the equatorial mode of the Tropical Atlantic in different oceanic reanalyses - Júnior, Paulo Sergio da Silva (2019)
In the Tropical Atlantic Ocean, the main mode of SST variability is the Atlantic Equatorial Mode or Atlantic Niño, which is strongly associated with rainfall patterns in northeastern Brazil and the West Africa Monsoon. The region of largest interannual variability, where the Atlantic Cold Tongue forms, is also a region of consistent biases in climate models. In this study, we investigate the interannual variability of the Tropical Atlantic and its changes in the recent decades in terms of the Bjerknes Feedback Index in a set of seven ocean reanalyses for the periods 1980-1999 and 2000-2010 and for an XX century ocean reanalysis for 1950-2010. Warming trends are observed in SSTs in the cold tongue region, as well as a decrease interannual variability. These in turn are associated with a weakening in the Bjerknes Feedback in the early XXI century, resulting from a stronger thermal damping and weaker thermocline feedback, associated with a weaker response of equatorial zonal thermocline slope to equatorial zonal wind stress. However, the spread among the reanalysis products is large, which makes necessary the use of multiple products and an ensemble analysis to minimize errors and obtain more robust results. This is further reinforced as no significant shifts in the Bjerknes Feedback Index were found for the period previous to 1980, since only one reanalysis product covers this period and its individual errors are large.